IMPLIKASI LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN MOTIVASI INTRINSIK KARYAWAN TERHADAP KINERJA KARYAWAN PT PEGADAIAN (PERSERO) KANWIL VI MAKASSAR - Dirwan Dirwan (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of this study is To determine the influence of the work environment, leadership, and intrinsic motivation and effects to employee performance at PT Pegadaian (Persero) Regional Office VI Makassar. This research was conducted at PT. Pegadaian (Persero) Regional Office VI Makassar with sample 30 respondents who are employees of PT Pegadaian (persero) Regional Office VI Makassar. The variables of this research is the Working Environment (X1), Leadership (X2) Intrinsic Motivation (X3) and Employee Performance (Y). research using multiple linear regression analysis with data collection using the questionnaire. Results of this research is the work environment does not significantly affect the performance of the employee, Leadership Style and Intrinsic Motivation significant influence on employee performance. and the leadership style variable is a variable that dominant influence on the dependent variable.